2006
DOI: 10.5688/aj7005117
|View full text |Cite
|
Sign up to set email alerts
|

Peer-Mentoring Workshop for Continuous Professional Development

Abstract: Objective. To develop a Professional Skills Enhancement Workshop (PSEW) to assist practitioners who require skills training to maintain competency and meet new standards of practice. Participants for this workshop were identified as those pharmacists who completed the peer review assessment process and who did not meet standards of practice expectations. Design. The full-day workshop consists of a half-day introduction to use of clinical drug information resources and approaches to addressing practice-based qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…[13][14][15][16][17] In a 2009 survey of US colleges and schools of pharmacy, Sturpe identified 32 programs using OSCEs, only 4 of which incorporated OSCE as an assessment tool in therapeutic courses. 18 Pharmacy OSCEs are also frequently used in laboratory courses, advanced pharmacy practice experience (APPE), yearly summative examinations, 11,[19][20] continuing education, 21 and licensure. 13,18 Medical schools have used OSCEs as a component to evaluate PBL for decades.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] In a 2009 survey of US colleges and schools of pharmacy, Sturpe identified 32 programs using OSCEs, only 4 of which incorporated OSCE as an assessment tool in therapeutic courses. 18 Pharmacy OSCEs are also frequently used in laboratory courses, advanced pharmacy practice experience (APPE), yearly summative examinations, 11,[19][20] continuing education, 21 and licensure. 13,18 Medical schools have used OSCEs as a component to evaluate PBL for decades.…”
Section: Introductionmentioning
confidence: 99%
“…Austin et al (2006) showed that 69% of Canadian pharmacists found not to be meeting standards of practice were helped by a Peer-Mentoring workshop and able to pass a peer review rechallenge process after completing the workshop.…”
Section: Physiotherapy and Cpdmentioning
confidence: 99%
“…10 It also prompted the regulatory body to engage in education/remediation for those practitioners who were not able to meet competency standards through the assessment process. 11 Meeting or exceeding standards in the peer review process was viewed as demonstration of the success of the pharmacist's continuing professional development activities and approaches. Those pharmacists who successfully completed the assessments were holistic assessment.…”
Section: Development Of a Peer-review Competency Assessment Processmentioning
confidence: 99%
“…While general acceptance and satisfaction is strong, and specific learning of new skills has occurred, 11 it is less clear whether this has actually translated into behavioral change of pharmacists and whether any behavioral change has actually resulted in improved outcomes for patients (e.g., decrease in drug therapy problems or errors). Anecdotally, pharmacists have reported that the act of preparing for the Practice Review results in new learning that translates into behavioral change; 11 whether this learning and change sustain beyond the immediate period of the Review itself is not known.…”
Section: 20mentioning
confidence: 99%